2023
DOI: 10.3390/bioengineering10020266
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Physiologically Relevant 3D Helicoidal-Oriented Cardiac Model: Simultaneous Application of Mechanical Stimulation and Surface Topography

Abstract: Myocardium consists of cardiac cells that interact with their environment through physical, biochemical, and electrical stimulations. The physiology, function, and metabolism of cardiac tissue are affected by this dynamic structure. Within the myocardium, cardiomyocytes’ orientations are parallel, creating a dominant orientation. Additionally, local alignments of fibers, along with a helical organization, become evident at the macroscopic level. For the successful development of a reliable in vitro cardiac mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…70 In addition, the main stress and strain directions form an obvious helical structure at the macroscopic level. Navaee et al 71 performed periodic uniaxial mechanical stretching of the pre-aligned EHT to simulate the helical arrangement of tissues in vivo , which demonstrated that mechanical stimuli and surface morphology increased the neonatal CMs maturation markers α-actinin and connexin-43, and promoted their maturation and functions. Recently, Takada et al 72 constructed EHT with more uniform arrangement of CMs by implanting hiPSC-CMs into microprocessed fibronectin gels.…”
Section: Methods For Constructing Human Cardiac Organoidsmentioning
confidence: 99%
“…70 In addition, the main stress and strain directions form an obvious helical structure at the macroscopic level. Navaee et al 71 performed periodic uniaxial mechanical stretching of the pre-aligned EHT to simulate the helical arrangement of tissues in vivo , which demonstrated that mechanical stimuli and surface morphology increased the neonatal CMs maturation markers α-actinin and connexin-43, and promoted their maturation and functions. Recently, Takada et al 72 constructed EHT with more uniform arrangement of CMs by implanting hiPSC-CMs into microprocessed fibronectin gels.…”
Section: Methods For Constructing Human Cardiac Organoidsmentioning
confidence: 99%